Additional evidence of tigers (Panthera tigris altaica) as intermediate hosts for Toxoplasma gondii through the isolation of viable strains. (December 2022) - Ren, Hongjie; Yang, Liulu; Zhu, Niuping; Li, Junbao; Su, Chunlei; Jiang, Yibao; Yang, Yurong
Abstract: Toxoplasmosis is one of the most common zoonotic diseases in the world. Felines excrete Toxoplasma gondii oocysts, which play a key role in the transmission of this protozoon. Pathological diagnoses were performed on four carcasses of captive tigers collected from 2019 to 2021 in China, and T. gondii was surveyed using serology, molecular analysis, and aetiology. Striated muscle samples of the tigers (n = 4) were bioassayed in mice. DNA derived from T. gondii tachyzoites was isolated and characterized using PCR–RFLP. The pathological diagnoses revealed that ageing, declined immune function, liver, and kidney failures caused the deaths in the tigers examined. A modified agglutination test (cut–off: 1:25) revealed that IgG antibodies to T. gondii were 100% (4/4) in the captive tigers. Two viable T. gondii strains (TgTigerCHn3 and TgTigerCHn4) were isolated from tiger striated muscles and seeded on the Vero cell culture for further propagation . The genotypes of TgTigerCHn3 and TgTigerCHn4 were ToxoDB#20 and ToxoDB#2, respectively. The two strains were avirulent for Swiss mice, which matched the ROP18 and ROP5 gene alleles of TgtigerCHn3 (3/4) and TgtigerCHn4 (3/3). Few brain tissue cysts (0–213) were observed in the mice after inoculation with TgTigerCHn3 and TgTigerCHn4. This is the first documented isolation of T. gondii ToxoDB#20 and ToxoDB#2 from tigers. The results provide additional direct evidence of tiger as intermediate hosts for T. gondii . Tigers in the zoos may potentially transmit T. gondii to other animals and humans. Graphical abstract: Image 1 Highlights: Two viable T. gondii strains were isolated from two tigers. The higher T. gondii detection rate was striated muscle digestive fluid by PCR.